Archaeology of the Ryukyu Islands A Regional Chronology from 3000 B.C. to the Historic Period - Pearson, Richard (University of Hawai'i Press, 2018)
Archaeological excavations have produced findings showing many important relationships between the culture of the Ryukyu Islands and that of surrounding areas, especially the islands of Kyushu and Taiwan.The present study is a synthesis of findings from excavations in Kyushu and the Ryukyus, particularly those contributed by Japanese researchers published in the last decade and those resulting from recent fieldwork on the east coast of Taiwan. From his own excavations .and those of other archaeologists, the author has formulated phases of cultural development and has related them in a regional temporal framework. Included here is an extensive, detailed analysis of ceramic typology for southern Kyushu and proposed ceramic types and wares for the Ryukyus and Taiwan. The author suggests that cultural differences between Kyushu and the Ryukyus may have resulted from the isolation of small colonizing groups and through the interaction of the inhabitants with differing environments.An important contribution to the literature on Far Eastern prehistory, this book also places Ryukyuan culture in the context of related neighboring cultures, and it should be of interest to anyone concerned with East Asian cultural history.